2014
DOI: 10.1007/s00228-014-1772-0
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine serum concentrations in dopamimetic psychosis in Parkinson’s disease and related disorders

Abstract: We suggest an orienting indication-specific therapeutic reference range of 15-141 ng/ml among PD patients with dopamimetic psychosis. Therapeutic drug monitoring is recommended and might help to minimize the risk of adverse events by screening for unexpectedly high serum concentrations of clozapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The dose for this latter condition is 5- to 10-fold lower than in TRS. 15 Off-label uses of clozapine include treatment of schizophrenia in patients younger than 18 years, bipolar disorder, depressive disorders, borderline personality disorder, substance misuse disorders, suicidality, aggression, tardive dyskinesia and tardive dystonia. 16 The regulations surrounding the use of clozapine in TRS also apply to these latter groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The dose for this latter condition is 5- to 10-fold lower than in TRS. 15 Off-label uses of clozapine include treatment of schizophrenia in patients younger than 18 years, bipolar disorder, depressive disorders, borderline personality disorder, substance misuse disorders, suicidality, aggression, tardive dyskinesia and tardive dystonia. 16 The regulations surrounding the use of clozapine in TRS also apply to these latter groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…New research has shown that the indication-specific target plasma concentration for clozapine is between 15 and 141 ng/mL 24. SGAs, such as clozapine, are thought to treat hallucinations by blocking dopamine D 2 receptors in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Is it better to withhold the most efficacious drugs instead of closely monitoring these drugs' side effects? In a retrospective study of 35 PDP patients, the mean serum concentration of clozapine was much lower in PD patients than the mean concentration future science group www.futuremedicine.com reported in schizophrenic patients (77.9 vs 350-600 ng/ml) with no serious adverse events were documented related to clozapine [63]. Are frequent blood tests or the side effect profile the main barrier for a clozapine prescription?…”
Section: Should Clinicians Be Doing More To Address Pdp?mentioning
confidence: 91%